Weight estimation in adults during emergency care - a length-based, habitus-modified system - Mason, Shaun Michael Nairn (My University, 2019)
Background: Medical errors are a significant cause of morbidity and mortality, and a large portion of medical errors occur due to medication dose errors. Many drug doses are based on weight in adult patients and it is frequently difficult to weigh patients prior to emergency interventions. Doctors are notoriously poor at weight estimation. Much research has been devoted in the field of weight estimation in children and length-based tapes (e.g. PAWPER and Broselow tapes) have been shown to be effective at estimating weight in the emergency setting. Objectives: To validate the accuracy of a length based, habitus modified system in weight estimation; to assess the accuracy of weight estimates by health care providers; and to assess the accuracy of weight estimates by patients. Methods: This was a prospective study in which a convenience sample of 400 patients were enrolled. Researcher estimated patient weight. Patient estimated weight. Height, weight and body habitus recorded using tape measure, scale and observer estimate. Weight then estimated using pre-calculated formulae. The primary outcome measure for the study was PW20 within 20% for each estimate category- researcher estimate, participant estimate, and formula estimate. The secondary outcome measure for the study was PW10 for all of the abovementioned objectives. Results: A total of 398 patients were eligible for study. For the group habitus <3, error within 10% was 43.8%, and error within 20% was 93.3%. For the Habitus 3, error within 10% was 22.3, and error within 20% was 48.5%. For habitus >3, error within 10% was 19.8% and error within 20% was 43.8%. Overall accuracy within 10% was 22.9% and within 20% was 50.3%. Researcher estimates overall error within 10% was 67.1%, and within 20% was 93.2%. Conclusion: The height based, habitus modified system was shown to be inaccurate at estimating weight over the total study population, with the best accuracy achieved in the thin study population. Researcher and participant estimation was shown to be more accurate over the total study population.
A Research report submitted to the faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine, Johannesburg, 2018